Reactions and complexation properties of 1,6-diaminohex-3-yne and 1,4-bis(2-aminoethyl)benzene - Kunze, Andreas; Gleiter, Rolf; Rominger, Frank; Oeser, Thomas (Dalton transactions, 2002)
1,6-Diaminohex-3-yne (3) reacts with silver triflate to yield a complex consisting of two silver ions and two molecules of 2-(2′-aminoethyl)-1-pyrroline (6). The silver ions form bridges between the primary amino group of one ligand and the imino group of the 1-pyrroline heterocycle of the other ligand. X-Ray investigations confirm this structure and show that the triflate anions are placed above and below the center of the plane spanned by the organic ligands and the silver ions. The reaction of 1,4-bis(2-aminoethyl)benzene (4) with silver triflate yields in the solid state an infinite chain composed of 4 and Ag+. X-Ray investigations reveal a loop-like arrangement of the chain in the solid state.
Gesehen am 03.11.2020